Properties of polar mesospheric clouds from ACE satellite infrared spectra. (November 2019) - Jones, Scott C.; Bernath, Peter F.; Boone, Chris D.
Highlights: ACE-FTS data were searched for signatures of polar mesospheric clouds (PMCs). Using the T-matrix scattering code, ACE-FTS spectra were fit to obtain ice particle temperatures, shapes, and particle column densities. A new routine PMC data product will be available for the ACE mission. Abstract: An analysis of the Atmospheric Chemistry Experiment (ACE) infrared Fourier transform spectrometer (FTS) spectra for signatures of Polar Mesospheric Clouds (PMCs) has been carried out by looking for the O-H vibrational mode at  ≈ 3240 cm − 1 . PMCs are thought to be indicators of climate change in the mesosphere and have been found to be increasing in recent years. Additionally, there are a number of open questions about the microphysics of the clouds, and their physical properties such as temperature, density, and particle shape and size. ACE has access to the entire infrared spectrum, potentially providing more accurate retrievals of these parameters. Using the T-matrix scattering code, we have made fits to the 3 micron ACE-FTS spectra. The ACE data set yielded 1762 unique occultations; after accounting for false positives, 955 occultations were left. We assumed oblate spheroids with a fixed effective radius of 40 nm and a nominal cloud size of 200 km, and obtained reasonable distributions for temperature, axial ratio and particle density. We expect that the methods presented here will allow a new routine ACE PMC data product to be developed.